2015
DOI: 10.4149/gpb_2015003
|View full text |Cite
|
Sign up to set email alerts
|

Structure and binding efficiency relations of QB site inhibitors of photosynthetic reaction centres*

Abstract: Abstract. Many herbicides employed in agriculture and also some antibiotics bind to a specific site of the reaction centre protein (RC) blocking the photosynthetic electron transport. Crystal structures showed that all these compounds bind at the secondary ubiquinone (Q B ) site albeit to slightly different places. Different herbicide molecules have different binding affinities (evaluated as inhibition constants, K I , and binding enthalpy values, ∆H bind ). The action of inhibitors depends on the following pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Jones et al reported that the photocurrent was inhibited by atrazine and terbutryn and that the values of detection limits were 49 nM for atrazine and 8.3 nM for terbutryn [ 8 ]. Nagy et al reported inhibition constants for terbutryn and atrazine of 1.3 and 63 μM, respectively, when assayed against the photosynthetic reaction center isolated from R. sphaeroides [ 36 ]. Nagy et al further demonstrated that the three parameters (herbicide molecular structure, interaction between herbicide and quinone binding site, and protein environment) depended on the magnitude of the inhibitory effect of herbicides.…”
Section: Resultsmentioning
confidence: 99%
“…Jones et al reported that the photocurrent was inhibited by atrazine and terbutryn and that the values of detection limits were 49 nM for atrazine and 8.3 nM for terbutryn [ 8 ]. Nagy et al reported inhibition constants for terbutryn and atrazine of 1.3 and 63 μM, respectively, when assayed against the photosynthetic reaction center isolated from R. sphaeroides [ 36 ]. Nagy et al further demonstrated that the three parameters (herbicide molecular structure, interaction between herbicide and quinone binding site, and protein environment) depended on the magnitude of the inhibitory effect of herbicides.…”
Section: Resultsmentioning
confidence: 99%